Different Arbuscular Mycorrhizal Fungi Cocolonizing on a Single Plant Root System Recruit Distinct Microbiomes - Jiachao Zhou (American Society for Microbiology, 2020)
ABSTRACT Plant roots are usually colonized by various arbuscular mycorrhizal (AM) fungal species, which vary in morphological, physiological, and genetic traits. This colonization constitutes the mycorrhizal nutrient uptake pathway (MP) and supplements the pathway through roots. Simultaneously, the extraradical hyphae of each AM fungus is associated with a community of bacteria. However, whether the community structure and function of the microbiome on the extraradical hyphae differ between AM fungal species remains unknown. In order to understand the community structure and the predicted functions of the microbiome associated with different AM fungal species, a split-root compartmented rhizobox cultivation system, which allowed us to inoculate two AM fungal species separately in two root compartments, was used. We inoculated two separate AM fungal species combinations, (i) Funneliformis mosseae and Gigaspora margarita and (ii) Rhizophagus intraradices and G. margarita, on a single root system of cotton. The hyphal exudate-fed, active microbiome was measured by combining 13C-DNA stable isotope probing with MiSeq sequencing. We found that different AM fungal species, which were simultaneously colonizing a single root system, hosted active microbiomes that were distinct from one another. Moreover, the predicted potential functions of the different microbiomes were distinct. We conclude that the arbuscular mycorrhizal fungal component of the system is responsible for the recruitment of distinct microbiomes in the hyphosphere. The potential significance of the predicted functions of the microbial ecosystem services is discussed. IMPORTANCE Arbuscular mycorrhizal (AM) fungi form tight symbiotic relationships with the majority of terrestrial plants and play critical roles in plant P acquisition, adding a further dimension of complexity. The plant-AM fungus-bacterium system is considered a continuum, with the bacteria colonizing not only the plant roots, but also the associated mycorrhizal hyphal network, known as the hyphosphere microbiome. Plant roots are usually colonized by different AM fungal species which form an independent phosphorus uptake pathway from the root pathway, i.e., the mycorrhizal pathway. The community structure and function of the hyphosphere microbiome of different AM species are completely unknown. In this novel study, we found that arbuscular mycorrhizal fungi cocolonizing on single plant roots recruit their own specific microbiomes, which should be considered in evaluating plant microbiome form and function. Our findings demonstrate the importance of understanding trophic interactions in order to gain insight into the plant-AM fungus-bacterium symbiosis.